Dynamic model of vibropress apparatus (Modern Problems of Metallurgy, 2019)
At present, vibration processes are widely used in various fields of technology to produce so-called beneficial effects. For the treatment of metals by pressure (OMD), these effects are primarily associated with the production of finished metallurgical products with improved structurally-sensitive metal properties, surface quality, and low energy consumption during technological operations. The purpose of this work is to construct a dynamic scheme of a press installation and justify the synchronization parameters of exciters. The results of model studies of a vibro-press installation of the discontinuous nature of deformation of the metal being processed are presented. The problems of synchronization of rotation of rotors of exciters are investigated. The data obtained can be used to develop promising models of equipment involved in the production of metallurgical products with improved structural-sensitive properties of the metal.
Keywords: vibration process; working organ; press installation; vibrator; vibration table; inertial element